Pharmacokinetic/pharma-codynamic study of pralurbactam (FL058) combined with meropenem in a neutropenic murine thigh infection model - Huang, Zhiwei; Li, Wenfang; Zhang, Ruohao; Li, Yi; Li, Xin; Bian, Xingchen; Zheng, Shansong; Wang, Xinmei; Zhang, Ning; Gao, Cong; Guo, Beining; Wang, Zhenling; et al. (Frontiers in Microbiology, 2024)
IntroductionPralurbactam (FL058) is a novel β-lactamase inhibitor with good inhibitory activity on class A, C, and D β-lactamases. This study aimed to evaluate the pharmacokinetic/pharmacodynamic (PK/PD) relationship of pralurbactam/meropenem in a neutropenic murine thigh infection model.MethodsAfter 2-h infection, neutropenic mice was treated with meropenem every 2 h alone or in combination with pralurbactam at different dosing frequencies for 24 h, and the colony count in the thighs was determined before and after treatment. The maximum effect model was fit to the PK/PD relationship to determine the PK/PD index and targets for pralurbactam in combination with meropenem resulting in a static effect and 1-log10 kill.ResultsThe plasma drug concentration-time data demonstrated that the PK profiles of pralurbactam were consistent with a one-compartment model. Pralurbactam demonstrated a linear PK profile in mice plasma. The percent time of free drug above 1 mg/L (%fT > 1 mg/L) was the PK/PD index that best described the bacterial killing effect of pralurbactam/meropenem over 24 h. When the PK/PD index %fT > 1 mg/L reached 38.4% and 63.6%, pralurbactam/meropenem combination would achieve bacteriostatic effect and 1-log10 reduction against Klebsiella pneumoniae in thigh bioburden, respectively.ConclusionThese PK/PD data derived from mouse thigh infection models will be used to inform the optimal dosing regimen of pralurbactam/meropenem combination in clinical trials.